2009
DOI: 10.1017/s0031182008005167
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte invasion profiles are associated with a common invasion ligand polymorphism in Senegalese isolates ofPlasmodium falciparum

Abstract: S U M M A R YPlasmodium falciparum parasites use multiple ligand-receptor interactions to invade human erythrocytes. Variant expression levels of members of the PfRh and PfEBA ligand families are associated with the use of different erythrocyte receptors, defining invasion pathways. Here we analyse a major polymorphism, a large sequence deletion in the PfRh2b ligand, and erythrocyte invasion profiles in uncultured Senegalese isolates. Parasites vary considerably in their use of sialic acid-containing and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 37 publications
5
28
0
Order By: Relevance
“…Most clinical P. falciparum infections in these areas of West Africa contain a mixture of different parasite genotypes (35,36), so analysis of individual genotypes and replication of assays on parasite lines would require cloning and longer-term growth, with a potential for changes in phenotypes during culture adaptation. Slight differences in sampling dates between the countries over a 2-year period are unlikely to have caused variation here, as previous studies in The Gambia showed similar distributions of invasion phenotypes in population samples of mild clinical malaria isolates taken up to 6 years apart (20,21), and similar profiles have been seen in Senegal in successive years (25,26). It is possible that changes might be seen over longer periods if levels of endemicity and acquired immunity in particular populations are reduced by enhanced malaria treatment interventions.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Most clinical P. falciparum infections in these areas of West Africa contain a mixture of different parasite genotypes (35,36), so analysis of individual genotypes and replication of assays on parasite lines would require cloning and longer-term growth, with a potential for changes in phenotypes during culture adaptation. Slight differences in sampling dates between the countries over a 2-year period are unlikely to have caused variation here, as previous studies in The Gambia showed similar distributions of invasion phenotypes in population samples of mild clinical malaria isolates taken up to 6 years apart (20,21), and similar profiles have been seen in Senegal in successive years (25,26). It is possible that changes might be seen over longer periods if levels of endemicity and acquired immunity in particular populations are reduced by enhanced malaria treatment interventions.…”
Section: Discussionsupporting
confidence: 73%
“…It should be noted that this study involved comparisons of West African sites, and parasite populations are extensively connected in this large region of endemicity (35,39), so it is possible that parasites in other parts of the world might have different phenotypes, particularly in areas where there is little acquired immunity. However, the observed variation in each of the populations studied here covered most of the range seen in a nonstandardized comparison of data from different studies reported separately on more-diverse individual populations, including those from Asia and South America (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). A vaccine based on known parasite ligands involved in invasion would need to incorporate a broad range of alternative EBA and Rh proteins in order to be effective for use in any local population, unless an effective vaccine can be based on a ligand such as Rh5 which appears to be consistently required for invasion (7).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We observed variation in invasion pathways for ex vivo P. falciparum isolates from Thies, as we have previously reported (34,35) (Fig. 4A).…”
Section: Fig 2 Receptor Restriction Increases Inhibition Of Eba-175-esupporting
confidence: 81%
“…For PMR calculations in which Nm/T/Chymo treated parasitized donor cells are mixed 50:50 (v/v) with acceptor cells, multiplying by a factor of 2 accounts for the fact that only ½ of the cells in the well can be invaded [ 16 ]. If PMR is calculated using a non-enzyme treated culture (for example, if parasitized erythrocytes are directly cultured and parasitemia is measured at each reinvasion cycle) the factor of 2 is not used.…”
Section: Measuring In Vitro Invasion Inhibition By Antibodiesmentioning
confidence: 99%